(untitled) (Singaporean Journal of Business Economics and Management, 2026)
This study examines the relationship between green marketing awareness and consumer willingness to pay (CWP) for sustainable products in the post-COVID era, focusing on the economic implications of sustainable branding. Using a sample of 400 respondents and employing descriptive statistics, Pearson correlation, regression analysis, chi-square tests, and ANOVA, the study investigates how key factors price sensitivity (PS), perceived environmental benefits (PEB), brand trust in sustainability claims (BTSC), and post-COVID health and environmental concerns (PHEC) influence green marketing awareness (GMA) and consumer purchasing behaviour. The regression results reveal that price sensitivity is a significant positive predictor of GMA (B = 0.149, p = .005), indicating that cost-conscious consumers are more likely to engage with sustainable branding when it aligns with perceived long-term value and ethical appeal. Although other variables such as PEB, BTSC, PHEC, and CWP did not individually predict GMA at statistically significant levels, the ANOVA results confirm that these predictors collectively have a significant impact on green marketing awareness (F = 2.688, p = .021). Moreover, chi-square tests indicate significant associations between all variables and consumer willingness to pay (p < .05), underscoring the importance of trust, affordability, and post-pandemic health concerns in shaping green purchasing decisions. The findings highlight that sustainable branding is economically viable in the post-COVID marketplace, but its effectiveness depends on balancing environmental messaging with affordability and credibility. It is recommended that businesses enhance transparency in sustainability claims and adopt pricing strategies that make green products more accessible, thereby fostering stronger consumer engagement and loyalty.